Cost-Effectiveness Analysis Kloramfenikol Dan Seftriakson Untuk Pengobatan Demam Tifoid Pada Pasien Dewasa Di Rumah Sakit Sanglah Denpasar - Amelia Lorensia; Doddy de Queljoe; Made Dwike Swari Santi (Fakultas Farmasi, Universitas Surabaya, 2018)
The number of typhoid fever patient in Indonesia is still high. Typhoid fever can be treated by antibiotic therapy such as chloramphenicol and ceftriaxone. The purpose of this study was to compare the cost-effectiveness of chloramphenicol and ceftriaxone which was given to adult patients who were diagnosed with typhoid fever in Sanglah Denpasar Hospital. A comparative study between two alternatives was conducted using the hospital perspective. Retrospective method was used to collect data from patient medical records, who was diagnosed and hospitalized in Sanglah Denpasar Hospital during January 2017 until July 2018. The cost analysis was perform using cost-effectiveness grid and cost-effectiveness ratio (ACER) methods. Cost-effectiveness grid showed that dominant of ceftriaxone for patient with typhoid fever. ACER analysis for ceftriaxone was IDR 2,097,170.88 with effectivenes (length of stay) 4.27 days, and was IDR 2,097,170.88 with effectiveness (the time of reaching normal temperature) 2.42 days. ACER analysis for chloramphenicol was IDR 2,555,464.22 with effectivenes (length of stay) 10.22 days, and was IDR 2,555,464.22 with effectiveness (the time of reaching normal temperature) 3.44 days. ACER analysis showed lower degree of ceftriaxone and higher effectiveness based on length of stay and the time of reaching normal temperature. The conclusion of this study is that ceftriaxone is more cost-effective than chloramphenicol.